Generative Art and Computational Creativity Analysis on Features of “Processing.org” Programming Software: Bahasa Indonesia - Qanissa Aghara; Patriot Mukmin (Fakultas Seni Rupa dan Desain ITB, 2023)
Integrative development between arts, science, and technology is evident. The birth of the computer era has influenced these matters since the 1990s. In the twenty-first century, various novelties and possibilities in the realm of digital arts had surfaced, whether it be in the realm of art creation or art appreciation. In this paper, the authors aim to analyze the matter of creativity in digital art by observing and utilizing Processing. org, an integrated development environment (IDE) software based on JavaScript, commonly used for visual coding. Qualitative methodology through literature review, data observation, and discourse analysis were applied through this research. The data obtained consists of JavaScript syntax and visual outputs generated by the command prompts. In analyzing the obtained data, generative art theory and computational creativity theory were utilized. Throughout the analysis, authors managed to note several functions—or command prompts—in Processing.org as key features of generative art creation. From the analysis, we could conclude that Processing software, through its features, could accommodate the creation of generative art and apply the concept of p-creativity within the context of computational creativity. In this paper, the authors also note the importance of randomization features on visual outputs.